(untitled) - Huỳnh, Thị Ngọc Kiều (Cần Thơ, 2011)
The current study investigates whether English non-majored students apply the writing strategies in their writing process and the extent to which the students use these writing strategies. It also examines the relationship between the students’ writing strategies and their writing performance
Keywords: American Language,Kỹ năng học,Study Skills; Writing